KEDUDUKAN DEKLARASI PELEBURAN GENERASI MUDA FKPPI DAN FKPPI : Studi Kasus Pendirian Perkumpulan Generasi Muda Forum Komunikasi Putra-Putri Purnawirawan dan Putra-Putri TNI POLRI. - Berliana Chandra Dewi (2021)
Community organization is something inherent in society because it can easily convey aspirations, do something of interest or activity or just have something characteristic in its members for community activities. In community organizations, there is often a merger to combine two or more community organizations and create a new organization from the merger and create a supporting organization to facilitate activities or expand the goals of the organization. One example of an organization that made a declaration of fusion is the organization A and Organization B, which in their declaration agreed to merge but in the course of restructuring a polemic emerged in which the declaration of fusion carried out by the organization A and B was unilaterally annulled with this new Association organization using a library research method juridical normative, which is based on the rules and principles of norms that apply in the community. The results from this study are that consolidation declaration is not strong enough because the declaration is a soft law where the legal force is less binding like the hard law and there is no stance in the establishment of the legal entity so that the association's declaration cannot be canceled.